"Quantitative assessment of aquifer potential in near shore coastal region using geospatial techniques and ground penetrating radar". (5th November 2021) - Gopaiah, Manne; Saha, Rajarshi; Chandra Das, Iswar; Sankar, Gummapu Jai; Kumar, Kumranchat Vinod
Abstract: Freshwater potential in coastal aquifers is under constant threat due to salinity hazard from saltwater intrusion. The main focus of the present study is, quantitative assessment of freshwater pockets using ground penetrating radar (GPR) investigation coupled with geospatial data of a near shore coastal aquifer, in the east coast of India. This area is suffering from saltwater intrusion and over-exploitation of groundwater. Randomly collected GPR profiles, well information, remote sensing data and soil samples were analysed. The integration of these techniques and data sets provided a robust platform to assess/identify the freshwater columns. The results show the seasonal water table variation from 1 to 4.25 m in pre-monsoon and 0.5 to 2.5 m in post-monsoon below ground level (BGL). The freshwater/saltwater interface zone varies from 3 to 6.0 m and 3 to 7.4 m in pre and post-monsoon respectively. The seasonal variation of freshwater column ranges from 0.5 to 4.3 m (pre-monsoon) and 1.5 to 5.3 m (post-monsoon). Aquifer potential (AP) varies from 0.01 to 6.70 million cubic meters (mcm) and 1.05 to 12.8 mcm in pre and post monsoon respectively. This study illustrates the aquifer potential and the overall groundwater dynamics for groundwater resource management. Highlights: An integrated approach of GPR data analysis and geospatial techniques highlighted. Quantification of freshwater potential and saltwater-freshwater interface. Improved coastal freshwater zone management against saltwater intrusion.